Horsethief's moon [large type] - Paine, Lauran (Wheeler publishing large print western, 2011)
They arrived by stealth atop a sandstone cliff overlooking Long Grass Valley, prepared to steal Rafter W horses. Instead they decided to robe the safe the general store. Everything went exactly right-- at first.